Developing through playing: Exploring Educational Games Tools Bombik Puzzle Block and Pom-pom toward The Fine Motor Development of Preschool Aged Children - Intrisilaras, Sindi; Apriliyanti, Retno; Kustriyanti, Dwi (Indonesian Journal Publisher, 2025)
Fine motor skills are a development that requires eye and hand coordination. The impact of late fine motor skills is that children have difficulty coordinating hand and finger movements, decreased academic achievement and are less active. Fine motor stimulation can be done in various ways, one of which is through playing activities with educational game tools such as bombik puzzle and pom-pom. This studwi was to determine the effectiveness of bombik puzzle and pom-pom Educative Game stimulation on the fine motor development of preschool-age children at the Early Childhood Education in Sambiroto Village. This type of research was Quasi Experiment with Nonequivalent Control Group Design. The population of this study consisted of 50 children. The total sample was 34 children aged 3-4 years, divided into 2, namely 17 children in the bombik puzzle group and 17 children in the pom-pom group, using a purposive sampling technique. Before the bombic puzzle intervention the average was 5.53 and after the intervention it increased to 11.41. Before being given the intervention, the pom-pom average was 6.29 and after being given the intervention it increased to 9.12. The Mann Whitney test results obtained a p-value of 0.014There is a difference in the effectiveness of bombik puzzle and pom-pom stimulation where bombik puzzle stimulation is more effective than pom-pom in improving fine motor development of preschoolers.